1993
DOI: 10.1073/pnas.90.19.9070
|View full text |Cite
|
Sign up to set email alerts
|

Dominant expression of mRNA for prostaglandin D synthase in leptomeninges, choroid plexus, and oligodendrocytes of the adult rat brain.

Abstract: Glutathione-independent prostaglandin D synthase [prostaglandin-H2 D-isomerase; (5Z,13E)-(15S)-9a,lla-epidioxy-15-hydroxyprosta-5,13-dienoate D-isomerase, EC 5.3.99.2] is an enzyme responsible for biosynthesis of prostaglandin D2 in the central nervous system. In situ hybridization with antisense RNA for the enzyme indicated that mRNA for the enzyme was predominantly expressed in the leptomeninges, choroid plexus, and oligodendrocytes of the adult rat brain. (2) is responsible for biosynthesis of PGD2 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
147
1
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(165 citation statements)
references
References 26 publications
13
147
1
2
Order By: Relevance
“…Herein, we identified the prostaglandin D2 synthase (PGDS) gene as a specific marker of arachnoidal cells of rats, mice and human beings (Urade et al, 1993;Yamashima et al, 1997;Kawashima et al, 2001). We leveraged this marker to develop a new transgenic Cre strain to target Nf2 inactivation to PGDS-expressing cells and showed that they are the meningioma cell of origin capable of giving rise to both fibroblastic and meningothelial histological subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we identified the prostaglandin D2 synthase (PGDS) gene as a specific marker of arachnoidal cells of rats, mice and human beings (Urade et al, 1993;Yamashima et al, 1997;Kawashima et al, 2001). We leveraged this marker to develop a new transgenic Cre strain to target Nf2 inactivation to PGDS-expressing cells and showed that they are the meningioma cell of origin capable of giving rise to both fibroblastic and meningothelial histological subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme responsible for PGD2 synthesis in the brain, lipocalin-type PGD synthase, is expressed in the leptomeninges (Urade et al, 1993;Beuckmann et al, 1997), similar to the DP receptor. Although the enzyme was also highly expressed in choroid plexus and oligodendrocytes of the brain (Urade eta!., 1993), DP receptor mRNA was not detected in these tissues and cells, as examined by RT-PCR and in situ hybridization analyses (data not shown).…”
Section: Dp Receptor In Brainmentioning
confidence: 99%
“…L-PGDS is produced in the choroid plexus and leptomeninges (Urade et al 1993) and has been well studied in association with the regulation of sleep-wake cycle (Qu et al 2006) and sensitivity to tactile pain (Eguchi et al 1999). It also plays a protective, anti-inflammatory role in some neurological disorders such as Alzheimer's disease (Kanekiyo et al 2007) and cerebral ischemia (Saleem et al 2009).…”
Section: Introductionmentioning
confidence: 99%